19.8k views
4 votes
Add and turn to simplest form.

Add and turn to simplest form.-example-1
User Ozzy
by
5.4k points

2 Answers

4 votes

Answer:

56

Explanation:

User Courtney Faulkner
by
5.2k points
3 votes

Answer:

The answer is


43 √(10)

Explanation:


5 √(490) + 4 √(40)

First of all we must make sure that the surds have equal roots

For 5√490


5 √(490) = 5 √(49 * 10 ) \\ = 5 * √(49) * √(10) \\ = 5 * 7 √(10) \\ = 35 √(10)

For 4√40


4 √(40) = 4 * √(4 * 10) \\ = 4 * √(4) * √(10) \\ = 4 * 2 √(10) \\ = 8 √(10)

So we have


35 √(10) + 8 √(10)

Using the rules of surds simplify the expression

That's


a √(x) + b √(x) = (a + b) √(x)

So we have


35 √(10) + 8 √(10) = (35 + 8) √(10) \\

We have the final answer as


43 √(10)

Hope this helps you

User Faradey Inimicos
by
5.2k points